Potential genetic therapies based on m6A methylation for skin regeneration: Wound healing and scars/keloids - Luo, Xiao; Zhu, Shu; Li, Jia; Zeng, Ning; Wang, Haiping; Wu, Yiping; Wang, Le; Liu, Zeming (Frontiers in Bioengineering and Biotechnology, 2023)
Skin wound healing is a complex and multistage process, where any abnormalities at any stage can result in the accumulation of non-functional fibrotic tissue, leading to the formation of skin scars. Epigenetic modifications play a crucial role in regulating gene expression, inhibiting cell fate determination, and responding to environmental stimuli. m6A methylation is the most common post-transcriptional modification of eukaryotic mRNAs and long noncoding RNAs. However, it remains unclear how RNA methylation controls cell fate in different physiological environments. This review aims to discuss the current understanding of the regulatory pathways of RNA methylation in skin wound healing and their therapeutic implications with a focus on the specific mechanisms involved.